Paradoxes in The Approach to Faculty Remuneration in Private Universities - A. R. Alaverdov (Высшее образование в России)
The article discusses the existing practice of faculty remuneration in private universities and the possible directions of its improvement. The author substantiates the thesis that this category of institutions of higher professional education, instead of implementing innovative and truly effective technologies to motivate faculty staff uses “pseudo market” approach – to keep their average earnings at a level slightly higher than the same level in state universities. The negative consequence of this strategic approach is personnel demotivation and decrease of loyalty level because the remunerationschemes are unified and do not permit to take into consideration teacher’s individual achievements. The analysis shows that the existing faculty remuneration practice doesn’t ensure the balance between economic and social interests. The employers strive to get maximum efficiency from the faculty staff at minimal costs. The paper shows three possible models of faculty behavior in these conditions. All these models demonstrate personnel demotivation, which causes the loss of education quality. The paper gives recommendations for changing both the strategy and tactics ofmotivation of private universities faculty based on the implementation of self-financing approach and the calculation of the ratio of teacher’s personal effectiveness.